Determinate of Lending Behavior of Joint Venture Banks in Nepal - Gnawali, Bindu (Patan Prospective Journal, 2022)
The purpose of this research is to examine the lending behavior of Joint venture banks in Nepal. The independent factors in this study are AQR, CAR, ROA, CRR, BS, GDP, and inflation rate, and dependent variable in this research is TL.The secondary data was used from the annual reports of all joint venture banks throughout a five-year period, from 2017 to 2021. Using SPSS 25 version, descriptive as well as causal-comparative research designs have been useful to analyze and interpret this data. For the sample, all seven Joint Venture banks are utilized. It is best to employ the purposive sampling technique. It has been demonstrated how independent variables affect the dependent variable using multiple linear regression models. The findings indicate that CRR and BS have considerable positive effects on TL and significant favorable effects but CAR has negative and significant effect on TL. The effects of AQR, ROA, GDP, and inflation on TL are negligible. Similarly, AQR, CAR, and inflation have been negatively related to TL but ROA, CRR, BS, and GDP have been positively related to lending.